"Old School" Islet Purification Based on the Unit Gravity Sedimentation as a Rescue Technique for Intraportal Islet Transplantation—A Case Report. (31st July 2020) - Gołębiewska, Justyna E.; Gołąb, Karolina; Gorycki, Tomasz; Śledziński, Maciej; Gulczyński, Jacek; Żygowska, Iwona; Wolnik, Bogumił; Hoffmann, Michał; Witkowski, Piotr; Ricordi, Camillo; Szurowska, Edyta; Śledziński, Zbigniew; et al.
Here, we present a case that required a supplemental "old school" islet purification for a safe intraportal infusion. Following pancreas procurement from a brain-dead 26-year-old male donor (body mass index: 21.9), 24.6 ml of islet tissue was isolated after continuous density gradient centrifugation. The islet yield was 504, 000 islet equivalent (IEQ), distributed among the following three fractions: 64, 161 IEQ in 0.6 ml of pellet, 182, 058 IEQ in 10 ml, and 258, 010 IEQ in 14 ml with 95%, 20%, and 10% purity, respectively. After a 23-h culture, we applied supplemental islet purification, based on the separation of tissue subfractions during unit gravity sedimentation, a technique developed over 60 years ago ("old school"). This method enabled the reduction of the total pellet volume to 11.6 ml, while retaining 374, 940 IEQ with a viability of over 90%. The final islet product was prepared in three infusion bags, containing 130, 926 IEQ in 2.6 ml of pellet, 108, 079 IEQ in 4 ml of pellet, and 135, 935 IEQ in 5 ml of pellet with 65%, 40%, and 30% purity, respectively, and with the addition of unfractionated heparin (70 units/kg body weight). Upon the islet infusion from all three bags, portal pressure increased from 7 to 16 mmHg. Antithrombotic prophylaxis with heparin was continued for 48 h after the infusion, with target activated partial thromboplastin time 50–60 s, followed by fractionated heparin subcutaneous injections for 2 weeks. β-Cell graft function assessed on day 75 post-transplantation was good, according to Igls criteria, with complete elimination of severe hypoglycemic episodes and 50% reduction in insulin requirements. Time spent within the target glucose range (70–180 mg/dl) improved from 42% to 98% and HbA1c declined from 8.7% to 6.7%. Supplemental "old school" islet purification allowed for the safe and successful utilization of a robust and high-quality islet preparation, which otherwise would have been discarded.